Theology of Marine Ecosystems from the perspective of the Al-Qur'an and its relevance to Indonesia for Marine Areas Strengthening pursuant to Law No. 32 of 2014 - Khairunnas Jamal; Juliani Syafitri; Ali Akbar; Hidayatullah Ismail; Agustiar; Afrizal M; Muhammad Yasir (Pharos Journal of Theology)
The marine ecosystem plays a crucial role in maintaining environmental balance and supporting human life, as emphasised in the Qur’ān, which describes the sea as a manifestation of Allah’s greatness, a source of sustenance, and a domain for human exploration. However, challenges such as over-exploitation, pollution, and weak regulatory enforcement threaten its sustainability in Indonesia. Law No. 32 of 2014 on the Marine Environment aims to promote sustainable governance but faces obstacles, including overlapping authorities and insufficient community participation. This study employs a qualitative method with a thematic interpretation and normative juridical analysis to explore Qur’anic perspectives on marine ecosystems and their relevance to Indonesian marine regulations. The findings indicate that Qur’anic principles—justice (‘adl), environmental preservation (ḥifẓ al-bī’ah), and prohibition of damage (fasad)—align with strengthening preventive measures in marine law. Integrating Islamic environmental ethics can enhance ecological awareness and foster a more sustainable marine management framework.